Assessment of Coagulation Disorder in Women Taking Oral Contraceptives - Samsunnahar, -; Akhter, Qazi Shamima; Atiquzzaman, -; Akhter, Najneen; Begum, US Naima; Rahman, Farhana (Journal of Bangladesh Society of Physiologist, 2015)
Background: Oral contraceptive pill (OCP) is related to development of hypercoagulability and the risk of thromboembolic effects in women. Objectives: To assess the coagulability status in women taking oral contraceptives by estimation of plasma fibrinogen level and total count of platelets. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2012 to December 2012 on sixty apparently healthy female subjects aged 25 to 45 years taking OCPs for 1 to 10 years. Thirty subjects were 1 to 5 years user group and another 30 subjects were >5 to 10 years user group. They were collected from family planning clinics of Dhaka city. In addition, age matched 30 apparently healthy women of OCP nonusers were also studied as control. For assessment of coagulability state, plasma fibrinogen and total counts of platelet levels were estimated by automated coagulation analyzer and automated hematology analyzer. Statistical analysis was done by unpaired Students t test. Results: The mean (±SE) total count of platelet level was significantly higher (P<0.001) in contraceptive user group and plasma fibrinogen level was higher in users but it was not significant. Conclusion: This study concludes that OCP users had more tendency of hypercoagulability and therefore these women are at higher risk of thromboembolic effects. DOI: http://dx.doi.org/10.3329/jbsp.v9i1.22786 Bangladesh Soc Physiol. 2014, June; 9(1): 1-5